The Influence of International Education Standards on Transportation Management Practices - Larsen Barasa (Action Research Journal, 2024)
This research examines the impact of international education standards on transportation management practices, focusing on multimodal education in transportation institutes. Qualitative data were collected from 39 cadets studying multimodal transportation, logistics, transportation safety, and law and road management. The study found that while there is some alignment between curriculum content and international standards, challenges such as resource constraints, cultural differences, and language barriers hinder full compliance. However, cadets perceive adherence to international standards as crucial for their future career prospects in the transportation industry. The research highlights the importance of aligning educational practices with international standards to enhance the competence of transportation professionals and improve the sustainability of transportation management practices. This study contributes to the existing literature by providing insights into the influence of international education standards on transportation management practices, with implications for policymakers, educators, and practitioners in the transportation sector